Dakwah Digital dalam Komik Line Webtoon Laa Tahzan: Don’t Be Sad dalam Perspektif Semiotika - Ahmad Rofi Syamsuri; Sunaryanto; Afnan Nadjib Helmy (Dakwah Institut PTIQ Jakarta, 2023)
Line Webtoon comics can be used as a digital da'wah tool that conveys da'wah messages through a cultural approach. But the problem is, even though it can be used as a means of digital da'wah, Line Webtoon Comics actually develop through industrial interests and media capitalism. The industrialization process for Line Webtoon Comics can develop well because the process uses what is known as glocalization. This research analyzes the meaning of digital da'wah in the Line Web Comic Ton Laa Tahzan: Don't be Sad episodes #88 #89#90 and #116. The research method used is textual analysis with semiotic theory. This research found digital preaching in The Line Webtoon: Laa Tahzan Don't Be Sad in four episodes, namely using matchsticks, glasses, hijab, beach, translated text of the Koran and hadith. The markers used in the four episodes are Arno, Hatta, Uda Sheng, Aliya and Aya. The signs used are learning, discipline, knowledge, patience, honesty, not lying, the power of Allah SWT, piety, faith, power of Allah SWT, surrender to Allah SWT, mistakes towards Allah SWT, injustice towards Allah SWT. If we conclude, the meaning of digital preaching of this comic is divided into three important points, namely aqidah, morals and muamalah. The denotational meaning is the importance of knowledge, the importance of fasting, the meaning of the tarawih prayer rakat, and the prohibition of shirk towards Allah SWT. The current connotation means that Muslims have not yet developed knowledge, fasting that has not been practiced properly, conflict due to differences in the rakats of tarawih prayers, and shirk towards Allah SWT.